“Writing on the sand: The Pericope of the Adulterous Woman (PAW) from memory.” (Theological Kronos, 2020)
This article takes up some of the contributions of social and collective memory to the study of the text of the New Testament (NT) and specifically to that of the pericope of the woman caught in adultery, which will be added to the final redaction of the Gospel of John (JG), in chapter 8, and that therefore is posed as a late text from the Textual Criticism. In this sense, the text regains a new importance in light of the contributions of memory in the study of the NT, some of these contributions were already presented in a past article (Caicedo, 2019). Now, it is proposed, once these contributions of social memory have been taken up, to apply them more specifically to the study of the aforementioned pericope. This will imply giving a seeing in thecontext of the first centuries of Christianity and not only in the context of the JG, where it is located as part of the Discourse of the Tabernacles (TD) and in the context of Jesus’ confrontation with some Jews. Finally, some implications for a contextual reading of the pericope are presented, from the perspective of social and collective memory.
Keywords: social and collective memory; New Testament; Gos- pel of John; Jesus and the woman caught in adultery